1986
DOI: 10.1126/science.232.4753.975
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate and Nitrate Concentrations from a South Greenland Ice Core

Abstract: An ice core in south Greenland covering the period 1869 to 1984 was analyzed for oxygen isotopes and chloride, nitrate, and sulfate concentrations. The data show that the "excess" (nonsea-salt) sulfate concentration has tripled since approximately 1900 to 1910 and the nitrate concentration has doubled since approximately 1955. The increases may be attributable to the deposition of these chemical specis from air masses carrying North American and Eurasian anthropogenic emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(77 citation statements)
references
References 17 publications
10
66
0
1
Order By: Relevance
“…1). The above trend in pH is also consistent with SO 2− 4 and NO − 3 trends in Greenland ice cores (Mayewski et al, 1986). Based on these sensitivity studies, all other simulations assume a cloud pH of 5.0 except for the PD Northern Hemisphere where the pH is 4.5.…”
Section: Global Oxidantssupporting
confidence: 56%
See 1 more Smart Citation
“…1). The above trend in pH is also consistent with SO 2− 4 and NO − 3 trends in Greenland ice cores (Mayewski et al, 1986). Based on these sensitivity studies, all other simulations assume a cloud pH of 5.0 except for the PD Northern Hemisphere where the pH is 4.5.…”
Section: Global Oxidantssupporting
confidence: 56%
“…Cloud water pH on the PD-PI timescale is impacted by anthropogenic emissions of sulfuric and nitric acid precursors in the Northern Hemisphere. In the Northern high latitudes the acidity of precipitation has increased since the PI (Mayewski et al, 1986), while there has been no change in the Antarctic. Cragin et al (1987) showed that a South Pole ice core spanning the past 2000 years has an average pH of 5.37 ± 0.08 with no trend in time.…”
Section: Model Limitationsmentioning
confidence: 99%
“…These measurements (Greenland ice core; Mayewski et al, 1986) show an increase in nsssulfate and nitrate concentration by a factor of 2.8 (from 30 to 84 µg kg −1 ) and 2.1 (from 55 to 115 µg kg −1 ), respectively, since preindustrial times that is lower than the calculated increase by the model (3.9 and 6.4, respectively). Although both measurements and model results are associated with large uncertainties, they indicate that significant changes have occurred both in oxidant levels and in aerosol composition since preindustrial era.…”
Section: Aerosol Burdenmentioning
confidence: 94%
“…It is not unexpected that alpine glacial meltwater contains NO 3 -, as glaciers accumulate a range of atmospherically delivered chemicals (12,33). NO 3 -is also among the first ions to elute from melting glacier ice (34).…”
Section: Low Nomentioning
confidence: 99%